ANALISIS USAHA PENGOLAHAN AMPLANG IKAN PIPIH (Notopterus chilata) SKALA RUMAH TANGGA DI KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Saptami Utami Evi; Emmy Sri Mahreda Sri Mahreda; Tri Dekayanti (Fish Scientiae, 2019)
Flat fish processing business amplang household in the city of Palangka Raya for future business development very well with the support of continuous availability of raw materials and capital flat fish are disbursed by the government in cash, business equipment and training for entrepreneurs to be able to continuedeveloped.The research was conducted in the City of Palangka Raya CentralKalimantan Province. The data used were primary and secondary data. The method used in processing and analyzing data in this study was purposive sampling. Amplang flat fish processing business households profit of Rp. 12,169 million, - peryear. From the field indicate the fact that this business remains favorable withsurvival in a long time.Based on the value of financial analysis using the criteria of investment NetBenefit Cost Ratio (BCR Net) 5% = 3.032073039 and Net B / C ratio of 13.5% =1.526361382 is greater than 1 means that the business is feasible to proceed.Especially for flat fish processing business amplang (Notopterus chilata) house hold in the city of Palangka Raya Central Kalimantan Province amplang demand for fish products by offering the same flat or D = S; means ampalng fish production to meet market flat.